Motor Unit Discharge Characteristics and Conduction Velocity of the Vastii Muscles in Long-Term Resistance-Trained Men - Škarabot, Jakob; Folland, Jonathan P.; Forsyth, Jules; Vazoukis, Apostolos; Holobar, Aleš; Del Vecchio, Alessandro (Medicine and science in sports and exercise, 2023)
PURPOSE: Adjustments in motor unit (MU) discharge properties have been shown after short-term resistance training; however, MU adaptations in long-term resistance-trained (RT) individuals are less clear. Here, we concurrently assessed MU discharge characteristics and MU conduction velocity in long-term RT and untrained (UT) men. METHODS: Motor unit discharge characteristics (discharge rate, recruitment, and derecruitment threshold) and MU conduction velocity were assessed after the decomposition of high-density electromyograms recorded from vastus lateralis (VL) and vastus medialis (VM) of RT (>3 yr; n = 14) and UT ( n = 13) during submaximal and maximal isometric knee extension. RESULTS: Resistance-trained men were on average 42% stronger (maximal voluntary force [MVF], 976.7 ± 85.4 N vs 685.5 ± 123.1 N; P < 0.0001), but exhibited similar relative MU recruitment (VL, 21.3% ± 4.3% vs 21.0% ± 2.3% MVF; VM, 24.5% ± 4.2% vs 22.7% ± 5.3% MVF) and derecruitment thresholds (VL, 20.3% ± 4.3% vs 19.8% ± 2.9% MVF; VM, 24.2% ± 4.8% vs 22.9% ± 3.7% MVF; P ≥ 0.4543). There were also no differences between groups in MU discharge rate at recruitment and derecruitment or at the plateau phase of submaximal contractions (VL, 10.6 ± 1.2 pps vs 10.3 ± 1.5 pps; VM, 10.7 ± 1.6 pps vs 10.8 ± 1.7 pps; P ≥ 0.3028). During maximal contractions of a subsample population (10 RT, 9 UT), MU discharge rate was also similar in RT compared with UT (VL, 21.1 ± 4.1 pps vs 14.0 ± 4.5 pps; VM, 19.5 ± 5.0 pps vs 17.0 ± 6.3 pps; P = 0.7173). Motor unit conduction velocity was greater in RT compared with UT individuals in both VL (4.9 ± 0.5 m·s -1 vs 4.5 ± 0.3 m·s -1 ; P < 0.0013) and VM (4.8 ± 0.5 m·s -1 vs 4.4 ± 0.3 m·s -1 ; P < 0.0073). CONCLUSIONS: Resistance-trained and UT men display similar MU discharge characteristics in the knee extensor muscles during maximal and submaximal contractions. The between-group strength difference is likely explained by superior muscle morphology of RT as suggested by greater MU conduction velocity.
CRIS-Team Scopus Importer:2023-04-28